Infliximab - İlgen Ertam Sağduyu (Galenos Publishing House, 2022)
Infliximab is a TNF-α inhibitor in the form of a chimeric monoclonal antibody. It received FDA approval in 2006 for the treatment of adult patients with severe chronic plaque psoriasis who developed side effects with conventional therapies or in whom these therapies were contraindicated or did not produce any response. Infliximab is administered via intravenous infusion, and infusion reactions are one of its common side effects. It is not suitable for intermittent treatment due to the high risk of infusion reaction, risk of developing antibodies, and loss of efficacy. Infliximab has the advantage of showing rapid clinical response in the treatment of unstable psoriasis and generalized pustular psoriasis.